The Relationship Of Provision Of Structured Assignments And Feedback On The Students Of Indonesian Learning Outcomes In Class X SMA 15 Maluku Tengah - Wa Mirna (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to determine whether there is a relationship between giving structured assignments and feedback on student learning outcomes in class X-4 SMA Negeri 15 Maluku Tengah on Indonesian language skills. This research is quantitative descriptive. The population of this study were students of class X-4 SMA Negeri 15 Maluku Tengah, amounting to 33 people. The results showed that the relationship between giving structured assignments and feedback on Indonesian language learning outcomes for X-4 graders of SMA Negeri 15 Maluku Tengah was satisfactory. This is evidenced by the number of respondents' answers to the questionnaire with a presentation of 70%-89%. The application of structured tasks with feedback can improve student learning outcomes. This has been proven by researchers in class X-4 students at SMA Negeri 15 Maluku Tengah. The results obtained based on the df value of 31 which was converted to rtable at a significance level of 5% obtained a price of 0.355, while at a 1% significance level a price of 0.456 was obtained. Test criteria: if rcount rtable then Ha is accepted and Ho is rejected, otherwise if rcount rtable then Ha is rejected and Ho is accepted. It turns out that rxy which is 0.74 is bigger than rtable. Because rxy is greater than rtable, then Ha is accepted and Ho is rejected. Based on the interpretation that is matched with the results of the calculation of the correlation index number "r" product moment with a large rxy (0.74) whose magnitude lies between 0.70 - 0.90. This means that the relationship between giving structured assignments and feedback on Indonesian language learning outcomes for class X SMA Negeri 15 Maluku Tengah students has a strong correlation, with a contribution of 54.76%. This shows that there is a relationship between giving structured assignments and feedback that has a positive effect on student learning outcomes.